IgA- and SIgA anti-PR3 antibodies in serum versus organ involvement and disease activity in PR3-ANCA-associated vasculitis. (25th February 2016) - Sandin, C; Eriksson, P; Segelmark, M; Skogh, T; Kastbom, A
Summary: Circulating immunoglobulin (Ig)A class anti-neutrophil cytoplasm antibodies (ANCA) directed against proteinase 3 (PR3) have been reported in ANCA-associated vasculitis (AAV) with mucosal involvement. However, secretory IgA (SIgA) PR3-ANCA has not been reported previously. In this study we compared serum levels of SIgA PR3-ANCA and IgA PR3-ANCA with IgG PR3-ANCA in relation to disease characteristics. Among 73 patients with AAV and PR3-ANCA at diagnosis, 84% tested positive for IgG PR3-ANCA, 47% for IgA-ANCA and 36% for SIgA PR3-ANCA at the time of sampling for the present study. IgA and IgG PR3-ANCA were represented similarly among patients with different organ manifestations, i.e. upper airway, lung or kidney at time of sampling. However, SIgA PR3-ANCA was significantly less represented among patients with upper airway involvement. During active disease, the proportions of IgA PR3-ANCA and SIgA PR3-ANCA-positive patients were significantly higher compared to inactive disease. Eight patients were sampled prospectively during 24 months from onset of active disease. In these patients, IgA PR3-ANCA and SIgA PR3-ANCA turned negative more often after remission induction compared to IgG PR3-ANCA. Our findings suggest that serum IgA PR3-ANCA and SIgA PR3-ANCA are related more closely to disease activity in AAV compared to IgG PR3-ANCA. Further studies are required to reveal if this has implications for disease activity monitoring. The mean number of PR3-ANCA isotypes increased along with disease activity, suggesting a global B cell activation during active disease.